A Conditional Time-Intervals formulation of the real-time Railway Traffic Management Problem. Issue 2 (2021) - Marlière, Grégory; Richard, Sonia Sobieraj; Pellegrini, Paola; Rodriguez, Joaquin
Abstract: This paper tackles the real-time Railway Traffic Management Problem (rtRTMP). It is the problem of finding an optimal choice for the train schedules and routes to reduce the delays of trains due to conflicts. We present a new Constraint Based Scheduling (CBS) formulation of the rtRTMP. This new formulation is based on the concept of conditional time-interval variables provided in the Ilog CP-optimizer library. A time-interval variable is the time interval in which an activity is executed, but it can also be a specific value "⊥" meaning the activity is non-executed. The new formulation exploits this new kind of variables and specific constraint propagation algorithms which contribute to the efficiency of the solution methods. The formulation has been validated with experiments on a large set of instances. The experimental results demonstrate the effectiveness of this new CBS model and show its good performance compared with the state-of-the art RECIFE-MILP algorithm.